EVENT-RELATED POTENTIAL (ERP) RESPONSES TO MUSIC AS A MEASURE OF EMOTION - Choy, Tsee Leng (My University, 2013)
This thesis examines how ERP responses to music provide an index of emotion in control, alexithymic, depressed and depressed alexithymic individuals using a musical affective priming task, with the objective being its clinical application to assess emotion in brain injured patients. Participants listened to pairs of music primes and music targets (music-music paradigm) and word targets (music-word paradigm) to mentally decide if they matched or not according to emotional valence (happy, sad). Responses manifested in the N300 (emotional categorization), P300 (emotional recognition) and N400 (emotional meaning) ERP components, with larger and more differentiated responses for the music-word paradigm indicating a less automatic nature than the music-music paradigm. Alexithymic individuals showed disrupted responses for all components for sad word targets, indicating a sequence of disconnects producing their decreased awareness of and difficulty with regulating emotion. Depressed participants displayed an emotional negativity bias for sad word targets in the P300 and N400, attributable to difficulty disengaging (cognitive rumination), reflecting how emotional deficits affect awareness. Disrupted P300 and N400 responses in the depressed alexithymic individuals were isolated to alexithymia rather than the emotional negativity bias. Specific processing deficits of happy music targets found only in depressed alexithymic individuals demonstrate how alexithymia increases the severity of depression. Although depression effects are more pervasive, alexithymia modifies depressive effects in emotional regulation. The P300 was most reliably seen in depression, and alexithymia to a lesser extent. Therefore, ERP responses to music can effectively and covertly measure emotion and different levels of automaticity, alexithymia and depression. This thesis is the first to demonstrate: 1) how music conveys emotion in a pure musical context (music-music); 2) musical emotion perception in alexithymia, depression and depressed alexithymia; 3) an effective non-verbal measure of emotion for assessing emotional states in brain injured populations.
Keywords: ERP; music; alexithymia; depression; P300; brain injury; Cognitive Neuroscience; Cognitive Neuroscience